2016
DOI: 10.1007/s10806-016-9633-8
|View full text |Cite
|
Sign up to set email alerts
|

Responding to a Public Health Objection to Vaccinating the Great Apes

Abstract: Capps and Lederman, in a paper published in this journal in 2015, argued that, at the time, the dismal circumstances of the Ebola outbreak in West Africa was an opportunity to revisit public health responses to emergent infectious diseases. Using a One Health lens, they argued for an ecological perspective-one that looked to respond to zoonoses as an environmental as well as public health concern. Using Ebola virus disease as an example, they suggested shared immunity as a strategy to vaccinate both humans and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Using a One Health paradigm, genomic sciences can contribute to the clinical and social responses to the environmental, economic, legal, and social determinants of health. In this regard, it is of critical importance that we build into that a mutual understanding of the ecological determinants of health that impact on all life [ 22 ]. A further step—justified under the One Health paradigm—will be progress in sharing the benefits of these technologies with non-human nature through innovations in these fields.…”
Section: A Hugo Vision For Ecogenomicsmentioning
confidence: 99%
“…Using a One Health paradigm, genomic sciences can contribute to the clinical and social responses to the environmental, economic, legal, and social determinants of health. In this regard, it is of critical importance that we build into that a mutual understanding of the ecological determinants of health that impact on all life [ 22 ]. A further step—justified under the One Health paradigm—will be progress in sharing the benefits of these technologies with non-human nature through innovations in these fields.…”
Section: A Hugo Vision For Ecogenomicsmentioning
confidence: 99%
“…Forty thousand dogs were also culled during these wide vaccination campaigns but it is unclear which stakeholder initiated this (Putra et al, 2013 ). From a OH perspective, vaccination potentially protects both animals and humans with very little risk, thus embodying a shared benefit approach that takes into account the interests of both humans and animals, and their interconnection (Capps & Lederman, 2015b , 2016 ; Edwards et al, 2018 ).…”
Section: The Ethics Of Cullingmentioning
confidence: 99%
“…Adopting the concept of ‘shared risks’ from the biomedical literature,16 Degeling et al also suggested that pursuing OH may mean that human beings carry a higher burden of risks in order to safeguard animal interests 15. Others have proposed and expanded on a conceptual idea of ‘shared benefits’ to justify and prioritise interventions that seek to benefit both humans and animal species over those that solely benefit humans, such as vaccination of apes to protect both them and humans against Ebola 17–20…”
Section: Does Oh Need An Ethic?mentioning
confidence: 99%